Survival of allochthonous bacteria in still mineral water bottled in polyvinyl chloride (PVC) and glass - Moreira, Leonilde (1994)
The mortality of Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae and Pseudomonas aeruginosa, based on the culturability of these bacteria, was assessed in non-carbonated mineral water, bottled in polyvinyl chloride (PVC) containing the indigenous flora, sterile mineral water bottled in PVC, sterile mineral water in glass containers, and sterile tap water in glass containers. There was a general decrease in the culturability of these organisms in the four test waters, except that Ps. aeruginosa grew in sterile tap water. Escherichia coli and Kl. pneumoniae had the highest mortality rates under the conditions tested, while Ent. cloacae had a very low and constant mortality rate that would have resulted in the persistence of this organism in mineral water for a long period of time. After a sharp initial decrease in culturability, Ps. aeruginosa also had a very low mortality rate in mineral water bottled in PVC.